Tea waste residue as low-cost biosorbent for treatment of 2 chlorophenol - Nornasuha, Abdullah; Nurul Aini, Razali; Muhammad Najmuddin, Mukhtar (Elsevier Ltd, 2022)
Tea (Camellia sinensis) is a healthy aromatic beverage and received high global demands, especially in the Asian region, and its residue resulted in huge biomass loss. In the present work, tea waste residue was pre-treated with acid solution and characterized by Nitrogen adsorption and Fourier transform infrared spectrum (FTIR). The prepared tea waste was used as an adsorbent to investigate its efficiency in removal of 2-Chlorophenol at various conditions, including times (0–70 min), initial 2-chlorophenol concentration (20–80 mg/L), tea waste dosage (0.2–0.5 g), pH (4–11) and temperature (30–50 °C). The results indicated that with 0.4 g of tea waste in a pH solution of 9 at 30 °C and a starting concentration of 40 mg/L of 2-Chlorophenol, the removal efficiency could reach 93.8 % after 60 min. This could be ascribed to the active hydroxyl ion that was considered the main active substance for the 2-Chlorophenol degradation process. This outcome proves to be highly effective with low-cost adsorbent material and positive effects on the environment.